2022
DOI: 10.3389/fnut.2021.738083
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dietary Omega-3 and Omega-6 Polyunsaturated Fatty Acids Level and Sarcopenia. A Meta-Analysis of Observational Studies

Abstract: Objective: This study investigates the relationship between dietary omega-3 and omega-6 polyunsaturated fatty acids (PUFAs) levels and sarcopenia.Methods: A comprehensive literature search in the databases of PubMed, Web of Science, and Embase (up to July 2021) were conducted to identify the observational studies on the relationship between dietary omega-3 and omega-6 PUFAs level and sarcopenia. The pooled odds ratio (OR) of sarcopenia for the highest vs. lowest dietary omega-3 and omega-6 PUFAs level and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Conversely, a meta‐analysis of observational studies suggested an inverse association between dietary nω3 fatty acid level and sarcopenia (odds ratio [OR] 0.41 [95% CI: 0.26–0.65, p = 0.0001]). This implies that a higher dietary intake of nω3 PUFAs may be associated with a lower risk of sarcopenia 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a meta‐analysis of observational studies suggested an inverse association between dietary nω3 fatty acid level and sarcopenia (odds ratio [OR] 0.41 [95% CI: 0.26–0.65, p = 0.0001]). This implies that a higher dietary intake of nω3 PUFAs may be associated with a lower risk of sarcopenia 53 …”
Section: Resultsmentioning
confidence: 99%
“…Calcitriol is the biologically active form of vitamin D. The activation of vitamin D is a tightly regulated process, and each step is essential for the production of the active form (calcitriol), which plays a crucial role in regulating the function of immune cells and maintaining a balanced immune response, which may help reduce inflammation and promote tissue repair. Vitamin D receptor agonists produce a decreased T‐helper 1 cell immune response (prominent in inflammation) and facilitates a regulatory T‐helper 2 cell phenotypic response 53 . Vitamin D deficiency is associated with the pathogenesis and increased severity of IIMs, MS, RA, systemic sclerosis and SLE 56 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, low dietary ω 3 -PUFA is observed in sarcopenia patients. In a recent meta-analysis, dietary ω 3 -PUFA reduced the risk of sarcopenia by 59% [odds ratio (OR) = 0.41, 95% confidence interval (95% CI): 0.26–0.65; P = 0.0001] [48]. Supplementation affected lean mass (effect size 0.27, 95% CI 0.04–0.51) and skeletal muscle mass (effect size 0.31, 95% CI 0.01–0.60) [49 ▪ ].…”
Section: Other Targetsmentioning
confidence: 99%
“…Moreover, within a larger-scale ( n = 125) clinical setting, dos Reis et al [19] reported a higher dietary LC n -3 PUFA intake, as measured by two 24-h food recalls conducted 6−10 days apart, to correlate with a lower risk of sarcopenia in kidney transplant patients, with this association driven by appendicular lean mass but not strength or physical function. Interestingly, a systematic review and meta-analysis of cohort studies reported an inverse relationship between high dietary LC n -3 PUFA intake and reduced prevalence of sarcopenia [20]. However, given that cohort studies do not infer causality, an exploration of RCTs is required.…”
Section: Cohort Studiesmentioning
confidence: 99%